MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN TEMATIK SEKOLAH DASAR DENGAN CONCEPT ATTAINMENT MODEL - Ni Putu Puspita Mayasari; I Wayan Suwira; Jaka Warsihna (IBERS : Jurnal Pendidikan Indonesia Bermutu, 2022)
This classroom action research aims to make students more able to understand the sub-theme The Importance of Maintaining Healthy Food Intake in Thematic Learning. The research was conducted in Semester 1 of the 2022/2023 Academic Year. Eight grade 5 students at SD Negeri 3 Riang Gede were used as research subjects. The research was carried out for two cycles, with each cycle consisting of planning, implementing, observing and evaluating results, as well as reflecting on the findings. Using learning achievement tests, direct descriptive qualitative and quantitative analyzes were used to collect and analyze data. Success is shown by the average KKM learning outcomes of 60.00 and completeness of 85.00 percent. The analysis produces the following results: 1) With an average acquisition of 53.75 in the Pre-Cycle, 60.63 in Cycle one, and 68.13 in Cycle two, the Concept Achievement Model can improve student learning outcomes; (2) By using the Concept Acquisition Model, student learning completeness can increase by 37.50 percent in Pre-Cycle, 75.00 percent in Cycle one, and 100.00 percent in Cycle two. The conclusion is that students can understand the sub-themes given.